Peninjauan Literatur Sistematis : Pemakaian Media Pembelajaran Digital dalam Mata Pembelajaran IPA di Tingkat Sekolah Dasar - Yusrina Maulidya Zahira; Ernita Vika Aulia; Muhammad Arif Mahdiannur (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The use of digital-based learning media has revolutionized the way we learn and teach. Particularly in teaching science at the elementary school level, the application of this type of media stands out as a relevant and interesting topic. This media can significantly improve the quality of science learning, while providing a more interactive and enjoyable learning experience for students. This study aims to review the literature related to the use of digital learning media in the context of science teaching. The approach used is a Systematic Literature Review (SLR). The data collection process involved compiling and analyzing articles discussing digital learning media in science learning, focusing on publications from 2021 to 2023. A total of six articles from journals available on Google Scholar were collected by the researcher. From a systematic review of various published studies, it can be summarized that various types of digital media can be applied in the science learning process. The most commonly used media include digital elements such as images, videos, simulations, and interactive games, as these tools can motivate students to learn and strengthen their curiosity about the material being studied.